Equations of Electrodynamics in a Hydrodynamic Medium with Regard for Nonequilibrium Fluctuations - Sokolovs'kyi, O. I.; Stupka, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We investigate the kinetics of the electromagnetic field in a hydrodynamic medium containing charged particles. A closed system of equations of the electromagnetic field and hydrodynamic equations taking into account dissipative processes is constructed. To describe the electromagnetic field, we use its average values and the corresponding binary correlation functions as new independent variables. The reverse influence of the field on the medium is studied. The investigation is based on quasirelativistic quantum electrodynamics in the Hamilton gauge and on the Bogolyubov method of reduced description of nonequilibrium processes.